The ValleyMorph Tool: An automated extraction tool for transverse topographic symmetry (T-) factor and valley width to valley height (Vf-) ratio - Daxberger, Heidi; Dalumpines, Ron; Scott, Darren M.; Riller, Ulrich (Computers & geosciences, 2014)
In tectonically active regions on Earth, shallow-crustal deformation associated with seismic hazards may pose a threat to human life and property. The study of landform development, such as analysis of the valley width to valley height ratio (Vf-ratio) and the Transverse Topographic Symmetry Factor (T-factor), delineating drainage basin symmetry, can be used as a relative measure of tectonic activity along fault-bound mountain fronts. The fast evolution of digital elevation models (DEM) provides an ideal base for remotely-sensed tectonomorphic studies of large areas using Geographical Information Systems (GIS). However, a manual extraction of the above mentioned morphologic parameters may be tedious and very time consuming. Moreover, basic GIS software suites do not provide the necessary built-in functions. Therefore, we present a newly developed, Python based, ESRI ArcGIS compatible tool and stand-alone script, the ValleyMorph Tool. This tool facilitates an automated extraction of the Vf-ratio and the T-factor data for large regions. Using a digital elevation raster and watershed polygon files as input, the tool provides output in the form of several ArcGIS data tables and shapefiles, ideal for further data manipulation and computation. This coding enables an easy application among the ArcGIS user community and code conversion to earlier ArcGIS versions. The ValleyMorph Tool is easy to use due to a simple graphical user interface. The tool is tested for the southern Central Andes using a total of 3366 watersheds. •We present a Python-based ESRI ArcGIS compatible tool, the ValleyMorph Tool, and stand-alone script.•The tool facilitates an automated extraction of the Vf ratio and the T-factor for large regions.•The tool provides output in the form of several ArcGIS data tables and shapefiles.•The tool is tested for the southern Central Andes using a total of 3366 watersheds.